Modelo de gestión para pagos por servicios ambientales del recurso hídrico como una alternativa de conservación al Páramo del pedregal, cantón mejía, provincia pichincha en el 2020-2021 - Cheza Asimbaya, José Patricio (2021)
Nowadays, moor ecosystems suffer anthropic alterations due to the accelerated advance of the agricultural frontier, generating a significant degradation of soil and water resources. The objective of this research was to design a management model for payments for environmental services of water resources (PSAH) as a conservation alternative for the Pedregal moor. This study is based on the method of Water Productivity Value based on the Opportunity Cost (Barrantes & Vega, 2001). In this way, surveys were carried out to identify the productive activities developed in the area and to calculate the net benefit. Prior to this, data provided by MAG, INAMHI and IGM were collected, processed and filtered to determine the current conditions of the moor. In fact, this area has different land uses, among the most representative are agricultural land with 74.80%, moorland with 10.16% and shrub vegetation with 4.89%. On the other hand, it has an available water supply of 39702597.5 m3/year, with a productivity value of $0.61 cents per m3. Therefore, it assumes a total value to be paid of $24,211,127.86 per year, for the 4971.28 ha available in the Pedregal moor. While the value to be paid per hectare per year is $4,870.20. Through the socialization with the delegates of the public entities of interest, about the management model for payments for environmental services of the water resource as an alternative for conservation of the moor. It was concluded that they are willing to put into practice, through an increase in the value to be paid in the consumption bills to the users of the parishes of Machachi and Aloasí. For this reason, these are viable mechanisms for the conservation of the environmental services provided by the high mountain ecosystem.